An in vivo and in vitro investigation of the effect of Aloe vera gel ethanolic extract using animal model with diabetic foot ulcer - Mohan Daburkar; Vikram Lohar; Arvind Singh Rathore; Pravin Bhutada; Shrikant Tangadpaliwar (Wolters Kluwer Medknow Publications, 2014)
Aim: To examine the preventive effect of Aloe vera gel ethanolic extract using diabetic foot ulcer (DFUs) protocol in Wistar rats. Materials and Methods: Male Wistar rats were divided into untreated control (Group I), untreated DFUs (Group II), DFUs treated with A. vera gel ethanolic extract (Group III), DFUs treated with topical A. vera gel (Group IV), DFUs treated with A. vera gel ethanolic extract and topical A. vera gel (Group V). The rats in the treatment groups were daily administered the A. vera gel and ethanolic extract for 9 days. Fasting blood glucose levels and percentage of wound ulcer contraction were measured on day 3, 6, and 9. Statistical Analysis used: The results are expressed as a mean ± Standard Error Mean (SEM). Data were analyzed using one-way analysis of variance (ANOVA) after Newman-Keuls test. P < 0.05 were considered statistically significant in all cases. Results: Oral administration of A. vera gel ethanolic extract at a dose of 300 mg/kg body weight per day to diabetic rats for a period of 9 days resulted in a significant reduction in fasting blood glucose and a significant improvement in plasma insulin. Topical application of A. vera gel at a dose 30 mg/kg body weight per day to streptozotocin (STZ)-induced diabetic rats for a period of 9 days resulted in no change in blood glucose and plasma insulin. Oral administration as well as topical application of A. vera gel ethanolic extract and gel significantly reduced the blood glucose, improved the plasma insulin, and significantly increased DNA and glycosaminoglycans (GAGs) to improve the wound ulcer healing as well as the breaking strength on day 9. Conclusions: Present findings provide a scientific rationale for the use of A. vera gel ethanolic extract, and showed that the gel attenuated the diabetic foot wound in rats.